Parity-related changes in serum biochemical profile, estrus response, and conception rate following double PGF2α estrus synchronization in Ettawa grade dairy goats - Rini Widyastuti; Sigit Prastowo; Akhmad Afifudin Al-Anshori; Faisal Amri Satrio (Universitas Airlangga, 2026)
Parity affects metabolic status and reproductive performance in female livestock. Since metabolic status can influence ovarian function and fertility, assessing serum biochemical profiles during estrus synchronization may help predict reproductive performance. This study assessed parity-related changes in serum biochemistry, estrus response, and conception rate following double prostaglandin F2α (PGF2α) estrus synchronization in Ettawa grade goats. A total of 24 goats were divided into three parity groups: low parity (0-1), medium parity (2-3), and high parity (4-5). All goats received two PGF2α injections at an 11-day interval. Serum samples were collected one day before the first injection (Day 0) and one day after the second injection (Day 12) to measure glucose, triglyceride, and cholesterol levels. The goats that exhibited estrus underwent double artificial insemination at a 12-hour interval, and conception was confirmed by ultrasonography 45 days after insemination. Following synchronization, the medium- and high-parity groups showed increased serum glucose levels (p< 0.05), while serum cholesterol levels were also increased in the medium- and high-parity groups (p< 0.05). After synchronization, serum triglyceride levels decreased in all groups (p< 0.05). The estrus response in the low-parity group was 12.5% lower than that in the medium- and high-parity groups; however, this difference was not statistically significant. The conception rate was over 80% in all groups. In conclusion, double PGF2α estrus synchronization resulted in parity-related changes in serum biochemistry, characterized by increased glucose and cholesterol levels and decreased triglyceride levels, while no significant differences in estrus response or conception rate were detected among the parity groups.